Modified current collector and preparation method thereof, composite metal lithium negative electrode and preparation method thereof, and secondary battery

The one-step method is used to prepare positively charged organic matter-lithium-philic metal composite modified three-dimensional current collector, which solves the problem of large volume changes and dendritic growth in the deintercalation process of metal lithium anode, significantly improves the circulation performance and stability, and improves the safety and circulation stability of the battery.

CN119517995APending Publication Date: 2025-02-25CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411720855.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

During the deintercalation process, the volume changes greatly, dendritic growth problems lead to failure and safety hazards. Existing modification methods such as homemade current collector process is complex and difficult to regulate, and cationic electrolyte additives are prone to local agglomeration under large currents, and their stability decreases.

Method used

Through a one-step preparation method, a positively charged organic-lithio metal composite modified three-dimensional current collector is prepared by using the coordination effect of cationic organic matter and inorganic metal salts, and is used to modify metal lithium negative electrodes. This method reduces the nucleation resistance of metal lithium and inhibits dendrites through the coordinated effect of lithium-philic inorganic substances and cationic organic substances.

Benefits of technology

It significantly improves the circulation performance and stability of the metal lithium negative electrode, reduces dendrite generation, and improves the safety and cycle stability of the battery. The half-cell can cycle stably for more than 150 turns or even more than 200 turns at a current density of 3 mA cm-2, with an average Coulomb efficiency of more than 99.0%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517995A_ABST
    Figure CN119517995A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a modified current collector, which comprises the following steps: (1) adding a cationic organic matter and an inorganic metal salt into a solvent to prepare a solution; and (2) adding a current collector into the solution, carrying out a reaction, overturning the current collector at set intervals in the reaction process, and washing and drying the current collector after the reaction to obtain the modified current collector. The preparation method comprises the following steps: preparing a positively charged organic matter-lithium-loving metal composite modified three-dimensional current collector by utilizing a coordination effect of a specific metal inorganic matter and a positively charged organic matter through a one-step method; through the coordination effect of the lithium-loving inorganic matter and the cationic organic matter, the cycle performance and the stability of the metal lithium negative electrode are jointly improved, the nucleation resistance of metal lithium can be reduced, the generation of lithium dendrites is inhibited, and the safety and the cycle stability of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery electrode materials, and specifically relates to the modification of current collectors, and the modification and application of composite metal lithium negative electrodes. Background Art

[0002] Lithium metal has a high theoretical specific capacity (3860 mAh g -1 ) and low reduction potential (-3.04 V, relative to standard hydrogen electrode). Compared with traditional graphite negative electrodes, secondary batteries using it as negative electrode have an absolute advantage in energy density, which can significantly improve the energy density of batteries and have great application prospects. However, the huge volume change and dendrite growth problems during the deintercalation of metal lithium will cause the metal lithium negative electrode to fail and even cause safety hazards.

[0003] Composite current collector structure design and lithium-philic modification are common modification methods for lithium metal anodes, such as constructing a three-dimensional current collector by combining nitrogen-doped fibers with lithium-philic metal (element / alloy / compound) particles (patent application CN 114520308 A), preparing a porous composite flexible substrate of polydimethylsiloxane and silver nanowires (patent application CN 114597364 A), and distributing a lithium-philic layer on the lower surface of the current collector (patent application CN 109088051 A), which can effectively reduce nucleation resistance and alleviate the volume expansion and dendrite growth of lithium metal. However, the process of making a self-made current collector is relatively complicated, and regulating the deposition of lithium metal under the current collector can only alleviate the volume expansion and dendrite growth of lithium metal for a limited time.

[0004] Cationic electrolyte additives (Dai H., et al. J. Am. Chem. Soc., 2018, 140(50): 17515-17521; Huang Z., et al. J. Am. Chem. Soc., 2020, 142(51): 21393-21403.) are also a common modification method for lithium metal anodes. The cations can be preferentially deposited on the protrusions where the negative charge of the interface electric field is concentrated, electrostatically shielding the uniform lithium ion deposition path and inhibiting dendrite growth. However, this type of additive is prone to local agglomeration under high current, resulting in decreased stability of the electrolyte additive, self-deposition, and failure of the electrostatic shielding effect. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a composite current collector for modifying a metal lithium negative electrode and a preparation method thereof.

[0006] To achieve the above objectives, this application proposes the following technical solutions: In a first aspect, a method for preparing a modified current collector is provided, comprising: (1) Adding cationic organic matter and inorganic metal salt into a solvent to prepare a solution; (2) adding a current collector to the solution to react, flipping the current collector at regular intervals during the reaction, and washing and drying the current collector after the reaction to obtain a modified current collector.

[0007] Furthermore, the cationic organic matter is one or more of positively charged pyridinium salts, imidazole salts, indole salts, quaternary ammonium salts, guanidine salts, polyacetimide and its derivatives and amino acids.

[0008] Furthermore, the inorganic metal is one or more of gold, silver, and zinc; and the inorganic metal salt is one or more of nitrate, acetate, chloride, sulfate, and citrate.

[0009] Furthermore, the molar ratio of the cationic organic matter to the inorganic metal salt is 1:1 to 100:1.

[0010] Furthermore, in the solution, the concentration of the inorganic metal salt is 0.002-0.05 mol / L.

[0011] Furthermore, in step (1), the raw materials for preparing the solution also include a reducing agent and / or a surfactant.

[0012] Furthermore, the surfactant includes one or more of polyvinyl pyrrolidone, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, hexadecyl trimethyl ammonium bromide and dodecyl trimethyl ammonium bromide.

[0013] Furthermore, the reducing agent includes one or more of ascorbic acid, sodium citrate and ethylenediamine.

[0014] Furthermore, the solvent includes one or more of water, ethylene glycol, ethanol, and organic ionic liquids; the organic ionic liquids are one or more of imidazole, pyridine, quaternary ammonium, quaternary phosphonium, and pyrrolidine ionic liquids.

[0015] Furthermore, the molar ratio of the reducing agent to the inorganic metal salt is 5:1 to 0.2:1.

[0016] Furthermore, the molar ratio of the surfactant to the inorganic metal salt is 5:1 to 1:200.

[0017] Furthermore, in step (2), the reaction temperature is 30-200°C.

[0018] Furthermore, in step (2), the reaction time is 1 to 120 min.

[0019] Furthermore, in step (2), the current collector is flipped every 5 to 600 seconds.

[0020] Furthermore, in step (2), the current collector is one or more of copper foil, copper mesh, foam copper, nickel foil, nickel mesh, foam nickel, carbon paper and carbon felt. In a second aspect, a modified current collector is provided, which is prepared using the aforementioned preparation method.

[0021] In a third aspect, a method for preparing a composite metal lithium negative electrode is provided, wherein lithium is deposited on the aforementioned modified current collector to obtain a composite metal lithium negative electrode.

[0022] In a fourth aspect, a composite metal lithium negative electrode is provided, which is prepared using the aforementioned preparation method.

[0023] In a fifth aspect, a secondary battery is provided, comprising the aforementioned composite metal lithium negative electrode.

[0024] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: The present invention utilizes the coordination effect of specific metal inorganic substances and positively charged organic substances to prepare a positively charged organic substance-lithiophilic metal composite modified three-dimensional current collector in one step. When the obtained modified current collector is used for a composite metal lithium negative electrode, the coordination effect of the lithium-philic inorganic substance and the cationic organic substance can jointly improve the cycle performance and stability of the metal lithium negative electrode, reduce the nucleation resistance of metal lithium, inhibit the generation of lithium dendrites, and improve the safety and cycle stability of the battery.

[0025] The modified current collector prepared by the preparation method of the present invention is applied to a metal lithium half-cell at 3 mA cm -2 It can stably cycle for more than 150 cycles or even more than 200 cycles at a current density of 1.577 W / m, and the average coulombic efficiency is greater than 99.0%. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 SEM images of the modified current collectors before and after lithium deposition in Example 1, Comparative Example 1 and Comparative Example 2, wherein (a) is the morphology of the modified current collector in Example 1 without lithium deposition, (b), (c) and (d) are the morphology of the modified current collector in Example 1 after 1, 3 and 10 mAh cm -2Lithium morphology. (e) is the morphology of the current collector in comparative example 1 without lithium deposition. (f), (g), and (h) are the morphology of the current collector in comparative example 1 with 1, 3, and 10 mAh cm-2 deposited respectively. -2 Lithium morphology. (i) is the morphology of the current collector in Comparative Example 2 without lithium deposition. (j), (k), and (l) are the morphology of the current collector in Comparative Example 2 with 1, 3, and 10 mAh cm-2 deposited respectively. -2 Lithium morphology.

[0028] Figure 2 This is the XRD diagram of the modified composite current collector of Example 1.

[0029] Figure 3 The XPS spectra of the modified composite current collector of Example 1, wherein (a) is the XPS high-resolution spectrum of Ag 3d at different etching times, and (b) is the atomic percentage diagram of Ag3d, C1s, Cu2p and N1s at different etching times.

[0030] Figure 4 It is a comparison chart of the half-cell cycle performance of Example 1, Example 2, Example 7 and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0031] The present invention provides a method for preparing a modified current collector, comprising: (1) Adding cationic organic matter and inorganic metal salt into a solvent to prepare a solution; (2) adding a current collector to the solution to react, flipping the current collector at regular intervals during the reaction, and washing and drying the current collector after the reaction to obtain a modified current collector.

[0032] In the present invention, cationic organic matter and lithium-philic inorganic matter are uniformly loaded on the current collector surface in situ through a one-pot method, and the organic matter and inorganic matter are tightly bound together through chemical bonds. The inorganic matter provides lithium-philic nucleation sites to reduce the nucleation resistance of metal lithium. The organic matter is a cationic organic matter with the same charge as the metal lithium ion, and the metal lithium deposition path is homogenized through electrostatic repulsion. Through the design of the organic / inorganic composite current collector, the electrochemical performance of the lithium metal battery is synergistically improved, and it is applied to the metal lithium half-cell at 3 mA cm -2 At a current density of 1.54 W, it can stably reach more than 150 cycles or even more than 200 cycles, and the average Coulomb efficiency is greater than 99.0%.

[0033] The inorganic metal is in-situ loaded on the surface of the current collector. The organic matter is cationic and can be bonded to the inorganic matter on the surface of the current collector through chemical bonds.

[0034] Inorganic metal salts include all metal salts that are lithium-philic after being reduced and deposited, including but not limited to nitrates, acetates, chlorides, sulfates, citrates, etc. containing gold, silver, zinc, etc.

[0035] In some embodiments, in step (1), the cationic organic compound has stable chemical properties and is one or more of positively charged organic salts, positively charged polyimide and its derivatives, and positively charged amino acids; the positively charged organic salts include pyridinium salts, imidazole salts, indole salts, quaternary ammonium salts, guanidine salts and other positively charged organic salts. More preferably, it is polyimide.

[0036] In some embodiments, in step (1), the molar ratio of the inorganic metal salt to the cationic organic matter is 1:1-1:100, more preferably 1:10-1:100, for example, 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, etc.

[0037] In some embodiments, in step (1), the inorganic metal salt is one or more of nitrates, acetates, chlorides, sulfates, and citrates of gold, silver, and zinc.

[0038] In some embodiments, in step (1), the raw materials for preparing the uniform solution further include a reducing agent and / or a surfactant.

[0039] In some embodiments, the surfactant includes one or more of polyvinyl pyrrolidone, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, hexadecyltrimethylammonium bromide, and dodecyltrimethylammonium bromide.

[0040] In some embodiments, the reducing agent includes one or more of ascorbic acid, sodium citrate, and ethylenediamine.

[0041] In some embodiments, the solvent includes one or more of water, ethylene glycol, ethanol, and ionic liquids.

[0042] In some embodiments, the molar ratio of the reducing agent to the metal salt is 5:1 to 0.2:1, for example, 5:1, 4:1, 3:1, 2:1, 1:1, 0.8:1, 0.5:1, 0.25:1, 0.2:1, etc.

[0043] In some embodiments, the molar ratio of the surfactant to the metal salt is 5:1 to 1:200, for example, 5:1, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1, 110:1, 120:1, 130:1, 140:1, 150:1, 160:1, 170:1, 180:1, 190:1, 200:1, etc.

[0044] In some embodiments, in step (2), the reaction temperature is 20-200°C, for example, 20°C, 40°C, 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, etc.

[0045] In some embodiments, in step (2), the reaction time is 1 to 120 min, for example, 1 min, 5 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, etc.

[0046] In some embodiments, in step (2), the current collector is flipped every 5 to 600 seconds, for example, every 5 seconds, 10 seconds, 20 seconds, 30 seconds, 60 seconds, 120 seconds, 180 seconds, 240 seconds, 300 seconds, 360 seconds, 420 seconds, 480 seconds, 540 seconds, 600 seconds, etc.

[0047] In some embodiments, in step (2), the current collector is one or more of copper foil, copper mesh, copper foam, nickel foil, nickel mesh, nickel foam, carbon paper and carbon felt.

[0048] In step (2), drying can be carried out by conventional drying methods in the art, such as vacuum drying, forced air drying, freeze drying, etc.

[0049] The present invention also provides a modified current collector, which is prepared by the above-mentioned preparation method.

[0050] The present invention also provides a method for preparing a composite metal lithium negative electrode, wherein lithium is deposited on the aforementioned modified current collector to obtain the composite metal lithium negative electrode.

[0051] The method of depositing lithium may adopt the conventional method of depositing lithium in the art, for example, the method of depositing lithium may be electrochemical deposition or molten lithium deposition.

[0052] Some embodiments of the present invention provide a composite metal lithium negative electrode, which is prepared using the aforementioned preparation method.

[0053] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.

[0054] Example 1 A method for preparing a composite lithium metal negative electrode comprises the following steps: (1) Weigh 0.85 mmol silver nitrate and 20 mmol polyimide respectively, add 100 mL deionized water to dissolve them and prepare a uniform solution; (2) Immerse the copper foam (4 cm×4 cm) washed with deionized water and ethanol into the prepared solution and react at 100°C. Flip the current collector every 2 minutes. After 40 minutes, terminate the reaction, wash the current collector with water, alcohol, and vacuum dry to obtain the modified composite current collector. The SEM image of the obtained composite current collector is shown in Figure 2. Figure 1 (a) shows the XRD pattern. Figure 2 As shown, from Figure 2 It can be seen that metallic silver is successfully loaded on the foam copper substrate; Figure 3 The XPS graph of the obtained composite current collector shows the signal peaks of Cu, Ag, C, and N. Figure 3 (a) It can be seen that as the etching time increases, the ratio of Ag and Cu in the composite current collector gradually increases, and the ratio of C and N decreases, indicating that polyimide is loaded on the surface of metal Ag and is gradually decomposed as the etching proceeds, resulting in a decrease in the ratio of C and N; Figure 3 As shown in (b), with the increase of etching time, the Ag 3d binding energy moves to the high field, indicating that there is an interaction between polyimide and metallic silver. Therefore, based on the composition, the composite current collector is named PEI@Ag@Cu; (3) Lithium is deposited on the modified current collector by an electrochemical method to obtain a composite metal lithium negative electrode.

[0055] Lithium was deposited on the resulting current collector with capacities of 1, 3, and 10 mAh cm -2 At this time, the SEM images are shown in 1(c), 1(d), and 1(e). Figure 1 (d) It can be seen that the deposition capacity reaches 10 mAh cm -2 It can be seen that there is still no precipitation of metallic lithium dendrites.

[0056] The current collector obtained in step (2) was used as the positive electrode and the lithium sheet as the negative electrode. A half-cell was assembled for charge and discharge tests. The discharge cut-off capacity was 1 mAh cm -2 , the charge cut-off voltage is 0.1 V, and the charge and discharge current density is 3 mA cm -2 , test the electrochemical performance.

[0057] The current collectors obtained in step (3) were used as positive and negative electrodes, and symmetrical batteries were assembled for charge and discharge tests. The charge and discharge current density was 1-5 mAh cm -2 , the charge and discharge cut-off capacity is 1~5 mAh cm -2 , test the electrochemical performance. Use the current collector obtained in step (3) as the negative electrode and lithium iron phosphate as the positive electrode to assemble a full battery for charge and discharge tests to test the electrochemical performance.

[0058] The half-cell assembled in Example 1 was-2 It can stably cycle 200 times at a current density of , and the average coulomb efficiency is 99.12%. Figure 4 shown.

[0059] The full battery assembled with the composite metal lithium negative electrode obtained in step (3) and lithium iron phosphate as the positive electrode can be stably cycled for more than 500 times at a current density of 1C, and the average coulombic efficiency is greater than 99.5%.

[0060] Comparative Example 1 The foam copper current collector was used as the positive electrode and the lithium sheet as the negative electrode. A half-cell was assembled for charge and discharge tests. The discharge cut-off capacity was 1 mAh cm -2 , the charge cut-off voltage is 0.1 V, and the charge and discharge current density is 3 mA cm -2 , test the electrochemical performance.

[0061] SEM image of copper foam current collector Figure 1 (e) shows that lithium is deposited on the copper foam current collector, and the capacity of metallic lithium is only 1 mAh cm -2 When the SEM image is Figure 1 As shown in (f), it can be seen from the figure that there is obvious precipitation of metal lithium dendrites. When the metal lithium capacity is 3 mAh cm -2 When the SEM image is Figure 1 (g) shows that when the capacity of metallic lithium is 10 mAh cm -2 When the SEM image is Figure 1 As shown in (h), it can be seen that with the increase of deposition capacity, the dendrites become more obvious. The obtained current collector was applied to metal lithium batteries, and the assembled half-cell was -2 It can only stably cycle 85 times at a current density of Figure 4 shown.

[0062] A full battery assembled with foam copper current collector as the negative electrode and lithium iron phosphate as the positive electrode can only be cycled stably 50 times at a current density of 1C.

[0063] Comparative Example 2 (1) Weigh 0.85 mmol of silver nitrate and add 100 mL of deionized water to dissolve it into a uniform solution; (2) Immerse the copper foam (4 cm × 4 cm) washed with deionized water and ethanol into the prepared solution and react at 100°C. Flip the current collector every 2 minutes. After 40 minutes, terminate the reaction, wash the current collector with water, alcohol, and vacuum dry for later use. The SEM image is shown in the figure. Figure 1 As shown in (i), the current collector is named Ag@Cu; (3) Lithium is deposited on the modified current collector by an electrochemical method to obtain a composite metal lithium negative electrode.

[0064] The current collector obtained in step (2) was used as the positive electrode and the lithium sheet as the negative electrode. A half-cell was assembled for charge and discharge tests. The discharge cut-off capacity was 1 mAh cm -2 , the charge cut-off voltage is 0.1 V, and the charge and discharge current density is 3 mA cm -2 , test the electrochemical performance.

[0065] Lithium was deposited on the resulting current collector, and the deposited lithium metal capacity was 1 mAh cm -2 When Figure 1 As shown in (j), no obvious dendrites were produced. When the metal lithium capacity was 3 mAh cm -2 When the lithium dendrites have begun to appear, the SEM picture is as follows Figure 1 (k) shows that when the capacity of metallic lithium is 10 mAh cm -2 When the SEM image is Figure 1 As shown in (l), it can be seen that as the deposition capacity increases, metallic lithium dendrites begin to precipitate.

[0066] The obtained current collector was applied to metal lithium batteries, and the assembled half-cell was -2 It can stably cycle for about 115 cycles at a current density of Figure 4 shown.

[0067] By comparing the electrochemical performance of the half-cells assembled in Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that the metal lithium half-cell in Example 1 has a high conductivity at 3 mA cm -2 The current density can be stable for more than 200 cycles, and the average coulomb efficiency is greater than 99.0%. The unmodified foam copper current collector in comparative example 1 can only be stably cycled for 80 cycles. Figure 1 Analysis shows that when a single silver compound is used to modify the current collector, the generation of lithium dendrites can be partially inhibited, but the effect is not obvious. After the current collector is compositely modified with an inorganic compound / organic cationic compound, the synergistic effect of the lithium-philic inorganic substance and the cationic organic substance in Example 1 can effectively inhibit the generation of metal lithium dendrites and improve the safety and cycle stability of the battery. After analysis, this may be because the lithium-philic inorganic substance can reduce the nucleation resistance of metal lithium, and the electrostatic shielding effect of the cationic organic substance homogenizes the metal lithium deposition path, and the two synergistically modify the electrochemical performance of the metal lithium battery.

[0068] Example 2 A method for preparing a composite lithium metal negative electrode comprises the following steps: (1) Weigh 0.85 mmol of silver nitrate and 20 mmol of polyimide, respectively, add 100 mL of deionized water to dissolve and prepare a uniform solution; (2) Immerse the copper foam (4 cm × 4 cm) washed with deionized water and ethanol into the prepared solution and react at 30°C. Turn the current collector over every 2 minutes. After 40 minutes, terminate the reaction, wash the current collector with water, alcohol, and vacuum dry for later use. (3) Lithium is deposited on the modified current collector by an electrochemical method to obtain a composite metal lithium negative electrode.

[0069] The current collector obtained in step (2) was used as the positive electrode and the lithium sheet as the negative electrode. A half-cell was assembled for charge and discharge tests. The discharge cut-off capacity was 1 mAh cm -2 , the charge cut-off voltage is 0.1 V, and the charge and discharge current density is 3 mA cm -2 The electrochemical performance was tested. The above-obtained current collector was applied to metal lithium batteries, and the assembled half-cell was -2 It can stably cycle for more than 175 times at a current density of .

[0070] Example 3 A method for preparing a composite lithium metal negative electrode comprises the following steps: (1) Weigh 0.85 mmol silver nitrate and 20 mmol polyimide, respectively, add 100 mL deionized water to dissolve and prepare a uniform solution; (2) Immerse the copper foam (4 cm × 4 cm) washed with deionized water and ethanol into the prepared solution and react at 60°C. Turn the current collector over every 2 minutes. After 40 minutes, terminate the reaction, wash the current collector with water, alcohol, and vacuum dry for later use. (3) Lithium is deposited on the modified current collector by an electrochemical method to obtain a composite metal lithium negative electrode.

[0071] The current collector obtained in step (2) was used as the positive electrode and the lithium sheet as the negative electrode. A half-cell was assembled for charge and discharge tests. The discharge cut-off capacity was 1 mAh cm -2 , the charge cut-off voltage is 0.1 V, and the charge and discharge current density is 3 mA cm -2 , test the electrochemical performance.

[0072] Example 4 A method for preparing a composite lithium metal negative electrode comprises the following steps: (1) Weigh 1.0 mmol of silver nitrate and 100 mmol of polyimide, respectively, and add 100 mL of deionized water to dissolve them into a uniform solution; (2) Immerse the copper foam (4 cm × 4 cm) washed with deionized water and ethanol into the prepared solution and react at 60°C. Turn the current collector over every 2 minutes. After 40 minutes, terminate the reaction, wash the current collector with water, alcohol, and vacuum dry for later use. (3) Lithium is deposited on the modified current collector by an electrochemical method to obtain a composite metal lithium negative electrode.

[0073] The current collector obtained in step (2) was used as the positive electrode and the lithium sheet as the negative electrode. A half-cell was assembled for charge and discharge tests. The discharge cut-off capacity was 1 mAh cm -2 , the charge cut-off voltage is 0.1 V, and the charge and discharge current density is 3 mA cm -2 , test the electrochemical performance.

[0074] Example 5 A method for preparing a composite lithium metal negative electrode comprises the following steps: (1) Weigh 1.0 mmol silver nitrate, 100 mmol polyimide, 1.0 mmol ascorbic acid, and 0.01 mmol polyvinyl pyrrolidone respectively, add 100 mL deionized water to dissolve them and prepare a uniform solution; (2) Immerse the copper foam (4 cm × 4 cm) washed with deionized water and ethanol into the prepared solution and react at 60°C. Turn the current collector over every 2 minutes. After 40 minutes, terminate the reaction, wash the current collector with water, alcohol, and vacuum dry for later use. (3) Lithium is deposited on the modified current collector by an electrochemical method to obtain a composite metal lithium negative electrode.

[0075] The current collector obtained in step (2) was used as the positive electrode and the lithium sheet as the negative electrode. A half-cell was assembled for charge and discharge tests. The discharge cut-off capacity was 1 mAh cm -2 , the charge cut-off voltage is 0.1 V, and the charge and discharge current density is 3 mA cm -2 , test the electrochemical performance.

[0076] Example 6 A method for preparing a composite lithium metal negative electrode comprises the following steps: (1) Weigh 0.85 mmol of silver nitrate and 40 mmol of lysine respectively, add 100 mL of deionized water to dissolve them and prepare a uniform solution; (2) Immerse the copper foam (4 cm × 4 cm) washed with deionized water and ethanol into the prepared solution and react at 60°C. Turn the current collector over every 2 minutes. After 40 minutes, terminate the reaction, wash the current collector with water, alcohol, and vacuum dry for later use. (3) Lithium is deposited on the modified current collector by an electrochemical method to obtain a composite metal lithium negative electrode.

[0077] The current collector obtained in step (2) was used as the positive electrode and the lithium sheet as the negative electrode. A half-cell was assembled for charge and discharge tests. The discharge cut-off capacity was 1 mAh cm -2 , the charge cut-off voltage is 0.1 V, and the charge and discharge current density is 3 mA cm -2 , test the electrochemical performance.

[0078] Example 7 A method for composite lithium metal lithium negative electrode comprises the following steps: (1) Weigh 0.85 mmol silver nitrate and 40 mmol histidine respectively, add 100 mL deionized water to dissolve and prepare a uniform solution; (2) Immerse the copper foam (4 cm × 4 cm) washed with deionized water and ethanol into the prepared solution and react at 60°C. Turn the current collector over every 2 minutes. After 40 minutes, terminate the reaction, wash the current collector with water, alcohol, and vacuum dry for later use. (3) Lithium is deposited on the modified current collector by an electrochemical method to obtain a composite metal lithium negative electrode.

[0079] The current collector obtained in step (2) was used as the positive electrode and the lithium sheet as the negative electrode. A half-cell was assembled for charge and discharge tests. The discharge cut-off capacity was 1 mAh cm -2 , the charge cut-off voltage is 0.1 V, and the charge and discharge current density is 3 mA cm -2 , test the electrochemical performance.

[0080] The obtained current collector was applied to metal lithium batteries, and the assembled half-cell was -2 It can stably cycle more than 200 times at a current density of .

[0081] Example 8 A method for composite lithium metal lithium negative electrode comprises the following steps: (1) Weigh 0.85 mmol silver nitrate and 40 mmol arginine respectively, add 100 mL deionized water to dissolve and prepare a uniform solution; (2) Immerse the copper foam (4 cm × 4 cm) washed with deionized water and ethanol into the prepared solution and react at 60°C. Turn the current collector over every 2 minutes. After 40 minutes, end the reaction, wash the current collector with water, alcohol, and vacuum dry for later use. (3) Lithium is deposited on the modified current collector by an electrochemical method to obtain a composite metal lithium negative electrode.

[0082] The current collector obtained in step (2) was used as the positive electrode and the lithium sheet as the negative electrode. A half-cell was assembled for charge and discharge tests. The discharge cut-off capacity was 1 mAh cm -2 , the charge cut-off voltage is 0.1 V, and the charge and discharge current density is 3 mA cm -2 , test the electrochemical performance.

[0083] Example 9 A method for composite lithium metal lithium negative electrode comprises the following steps: (1) Weigh 0.85 mmol chloroauric acid and 40 mmol histidine respectively, add 100 mL deionized water to dissolve and prepare a uniform solution; (2) Immerse the copper foam (4 cm × 4 cm) washed with deionized water and ethanol into the prepared solution and react at 60°C. Turn the current collector over every 2 minutes. After 40 minutes, terminate the reaction, wash the current collector with water, alcohol, and vacuum dry for later use. (3) Lithium is deposited on the modified current collector by an electrochemical method to obtain a composite metal lithium negative electrode.

[0084] The current collector obtained in step (2) was used as the positive electrode and the lithium sheet as the negative electrode. A half-cell was assembled for charge and discharge tests. The discharge cut-off capacity was 1 mAh cm -2 , the charge cut-off voltage is 0.1 V, and the charge and discharge current density is 3 mA cm -2 , test the electrochemical performance.

[0085] Example 10 A method for composite lithium metal lithium negative electrode comprises the following steps: (1) Weigh 1.0 mmol chloroauric acid, 40 mmol histidine, 1.0 mmol ascorbic acid, and 0.01 mmol polyvinylpyrrolidone respectively, add 100 mL deionized water to dissolve them and prepare a uniform solution; (2) Immerse carbon paper (4 cm × 4 cm) washed with deionized water and ethanol into the prepared solution and react at 60°C. Turn the current collector over every 2 minutes. After 40 minutes, terminate the reaction, wash the current collector with water, alcohol, and vacuum dry for later use. (3) Lithium is deposited on the modified current collector by an electrochemical method to obtain a composite metal lithium negative electrode.

[0086] The current collector obtained in step (2) was used as the positive electrode and the lithium sheet as the negative electrode. A half-cell was assembled for charge and discharge tests. The discharge cut-off capacity was 1 mAh cm -2 , the charge cut-off voltage is 0.1 V, and the charge and discharge current density is 3 mA cm -2 , test the electrochemical performance.

[0087] Embodiment 11 A method for composite lithium metal lithium negative electrode comprises the following steps: (1) Weigh 1.0 mmol chloroauric acid, 40 mmol histidine, 1.0 mmol ascorbic acid, and 0.01 mmol polyvinylpyrrolidone respectively, add 100 mL deionized water to dissolve them and prepare a uniform solution; (2) Immerse carbon paper (4 cm × 4 cm) washed with deionized water and ethanol into the prepared solution and react at 60°C. Flip the current collector every 10 seconds. After 5 minutes, terminate the reaction, wash the current collector with water, alcohol, and vacuum dry for later use. (3) Lithium is deposited on the modified current collector by an electrochemical method to obtain a composite metal lithium negative electrode.

[0088] The current collector obtained in step (2) was used as the positive electrode and the lithium sheet as the negative electrode. A half-cell was assembled for charge and discharge tests. The discharge cut-off capacity was 1 mAh cm -2 , the charge cut-off voltage is 0.1 V, and the charge and discharge current density is 3 mA cm -2 , test the electrochemical performance.

[0089] Example 12 A method for composite lithium metal lithium negative electrode comprises the following steps: (1) Weigh 1.0 mmol chloroauric acid, 40 mmol histidine, 1.0 mmol ascorbic acid, and 0.01 mmol polyvinylpyrrolidone respectively, add 100 mL deionized water to dissolve them and prepare a uniform solution; (2) Immerse carbon paper (4 cm × 4 cm) washed with deionized water and ethanol into the prepared solution and react at 60°C. Turn the current collector over every 2 minutes. After 120 minutes, terminate the reaction, wash the current collector with water, alcohol, and vacuum dry for later use. (3) Lithium is deposited on the modified current collector by an electrochemical method to obtain a composite metal lithium negative electrode.

[0090] The current collector obtained in step (2) was used as the positive electrode and the lithium sheet as the negative electrode. A half-cell was assembled for charge and discharge tests. The discharge cut-off capacity was 1 mAh cm -2 , the charge cut-off voltage is 0.1 V, and the charge and discharge current density is 3 mA cm -2 , test the electrochemical performance.

[0091] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a modified current collector, characterized in that: include: (1) Adding cationic organic matter and inorganic metal salt into a solvent to prepare a solution; (2) adding a current collector to the solution to react, flipping the current collector at regular intervals during the reaction, and washing and drying the current collector after the reaction to obtain a modified current collector.

2. The method for preparing the modified current collector according to claim 1, characterized in that: The cationic organic matter is one or more of positively charged pyridinium salts, imidazole salts, indole salts, quaternary ammonium salts, guanidine salts, polyacetimide and its derivatives and amino acids; The inorganic metal is one or more of gold, silver and zinc; the inorganic metal salt is one or more of nitrate, acetate, chloride, sulfate and citrate.

3. The method for preparing the modified current collector according to claim 1, characterized in that: The molar ratio of the cationic organic matter to the inorganic metal salt is 1:1 to 100:1; In the solution, the concentration of the inorganic metal salt is 0.002-0.05 mol / L.

4. The method for preparing the modified current collector according to claim 1, characterized in that: In step (1), the raw materials for preparing the solution also include a reducing agent and / or a surfactant; The surfactant comprises one or more of polyvinyl pyrrolidone, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, hexadecyl trimethyl ammonium bromide and dodecyl trimethyl ammonium bromide; The reducing agent includes one or more of ascorbic acid, sodium citrate and ethylenediamine; The solvent includes one or more of water, ethylene glycol, ethanol, and organic ionic liquids; the organic ionic liquid is one or more of imidazole, pyridine, quaternary ammonium, quaternary phosphonium, and pyrrolidine ionic liquids; The molar ratio of the reducing agent to the inorganic metal salt is 5:1 to 0.2:1; the molar ratio of the surfactant to the inorganic metal salt is 5:1 to 1:

200.

5. The method for preparing the modified current collector according to claim 1, characterized in that: In step (2), the reaction temperature is 30-200°C; Preferably, in step (2), the reaction time is 1 to 120 min; Preferably, in step (2), the current collector is flipped every 5 to 600 seconds.

6. The method for preparing the modified current collector according to claim 1, characterized in that: In step (2), the current collector is one or more of copper foil, copper mesh, foam copper, nickel foil, nickel mesh, foam nickel, carbon paper and carbon felt.

7. A modified current collector, characterized in that: The method is prepared according to any one of claims 1 to 6.

8. A method for preparing a composite metal lithium negative electrode, characterized in that: Lithium is deposited on the modified current collector as claimed in claim 7 to obtain a composite metal lithium negative electrode.

9. A composite metal lithium negative electrode, characterized in that: The preparation is obtained by the preparation method as claimed in claim 8.

10. A secondary battery, characterized in that: Comprising the composite metal lithium negative electrode as described in claim 9.

Citation Information

Patent Citations

  • A surface dendrite-free high-safety metal lithium anode and preparation method and application thereof

    CN109088051A

  • Lithium metal battery negative electrode and preparation method and application thereof

    CN114520308A

  • Preparation method of polydimethylsiloxane and silver nanowire porous composite flexible lithium metal battery

    CN114597364A

  • Method for preparing modified lithium cathode copper foil current collector and application thereof

    CN108767263A

  • Preparation and application of lithium metal anode with composite film

    CN110190243A